Introduction to social engineering (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. In his book How to Hack a Human: Cybersecurity for the Mind, security expert Raef Meeuwisse defines social engineering as ... the act of constructing relationships, friendships or other human interactions for the purpose of enticing the recipient to perform an inadvisable action or reveal secret information. In cybersecurity terms, this means preying on our emotional responses to make us voluntarily compromise our own security. In this track, we'll learn about social engineering attacks, the standard techniques used in them, and how we can protect ourselves against them. Learning Objectives Learn what social engineering is, and how it's specifically used in a cyber security context Learn about famous examples of social engineering hacks Learn about the techniques you must use to avoid falling prey to a social engineer.